2019
DOI: 10.1088/1742-6596/1351/1/012097
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Pepper Yields (Capsicum annuum L.) by Giving a Formulation of Biological Fertilizer of Cellulolytic Bacteria Based on Organic Liquid Waste

Abstract: Red pepper production in 2016-2017 was increased. Although production has increased, demand for pepper will continue to increase, and efforts to increase soil fertility still need to be sought. To maintain and increase soil productivity, a combination of inorganic fertilizers with appropriate organic fertilizers is needed. One of the organic fertilizers is biofertilizers. This research aimed at finding out the formulation and dosage of biological fertilizers consortium of cellulolytic bacteria based on organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
0
6
0
4
Order By: Relevance
“…Further test results of physiological response with DMRT test at a rate of 5% can be seen in Table 1. [8] which reported that the provision of some biofertilizer waste does not have an effect on some observation parameters on red chili. Based on the results of analysis of biofertilizers obtained pH and nutrients N, P and K can be seen in Table 2.…”
Section: Physiological Responsesmentioning
confidence: 98%
“…Further test results of physiological response with DMRT test at a rate of 5% can be seen in Table 1. [8] which reported that the provision of some biofertilizer waste does not have an effect on some observation parameters on red chili. Based on the results of analysis of biofertilizers obtained pH and nutrients N, P and K can be seen in Table 2.…”
Section: Physiological Responsesmentioning
confidence: 98%
“…Pada percobaan tanaman jamur bahwa secara tabulasi perlakuan pemberian air leri 60 ml/l air memberikan pertumbuhan dan produksi terbaik berat total seberat 285,77 g [9]. Hasil percobaan menunjukkan bahwa semua aplikasi pupuk hayati berbasis limbah cair organik selulolitik (limbah air cucian beras, limbah air kelapa dan limbah air tahu) mampu memberikan hasil yang bervariasi pada setiap parameter yang diamati sehingga semua limbah dapat diaplikasikan pada tanaman lada [16]. Hasil yang diperoleh dari penerapan POC air cucian beras sebanyak 500 ml memberikan respon terhadap hasil buah tomat servo [17].…”
Section: Pembahasanunclassified
“…Beberapa kegiatan yang telah dilakukan yaitu pembangunan canal blocking, pembuatan rumah kompos, dan pengadaan hewan ternak beserta kandang (Hapsoh et al, 2018). Dampak dari kegiatan pembangunan canal blocking tersebut menyebabkan terjadinya peningkatan produktivitas pertanian terutama tanaman padi pada tahun 2018 mencapai 7-8 ton/Ha (Dini et al, 2019), produksi cabai pada tahun 2018 mencapai 14-15 ton/Ha , dan pembuatan canal blocking meningkatkan beberapa parameter pertumbuhan dan produksi tanaman cabai (Hapsoh et al, 2019). Selain meningkatkan produktivitas tanaman, jumlah lahan sawit yang dikonversi menjadi lahan pertanian padi dan cabai terhitung sampai tahun 2018 sebesar 18 Ha dan ini akan terus terjadi peningkatan.…”
Section: Pendahuluanunclassified
“…Pada tanaman yang akan dibudidayakan pada demplot diaplikasikan pupuk organik dengan memanfaatkan limbah organik dan kotoran sapi yang ada di desa setempat dan pupuk hayati konsorsium bakteri selulolitik hasil penelitian tim pengabdian (Hapsoh et al, 2019;. Selain pemberian pupuk organik, pada demplot juga diaplikasikan pestisida organik dan agens hayati cendawan entomopatogen Beauveria bassiana Vuill hasil penelitian tim pengabdian .…”
Section: Pembuatan Pupuk Organik Untuk Keperluan Budidaya Tanaman Pada Demplotunclassified